Resistividade elétrica e absorção capilar de concretos compostos com cinza de lodo de ETA - Amaral, Fábio Dischkaln do (2015)
The construction sector has been one of the most comprehensive for the application of these residues, because it allows the reintroduction of industrial rejects in the composition of mortars and concretes. Byproducts such as sewage sludge ash (SSA), rice husk ash (RHA) and blast furnace slag (BFS) enable its use in concrete, conferring durability conditions. In this work were investigated mixtures containing different amounts of SSA, RHA and BFS, the apparent electrical resistivity as been made conforming to the four electrode method (Wenner), water capillary absorption, according to ABNT NBR 9779 and compressive strength, by ABNT NBR 5739. Ten binders have been tested, water/binder ratio 0,35, 0,50 and 0,65 and tree type of curing, wet curing periods of 7, 14, 28, 56 and 91 days and wet curing periods of three and seven days, tested at 28 and 91 days. The Portland cement substitutions by SSA varied from 0% to 30%, with further ternary mixture of 20% BFS and 5% SSA, 20% BFS and 10% SSA, and quaternary, SSA 15%, 5% BFS and 5% RHA. In relation to water capillary absorption tests, it was found that with the increase in the curing time of three to seven days there was reduction in absorption of water by capillarity. In the test of apparent resistivity occurred increased with the reduction of the water/binder and an increase in the degree of hydration where the best results were obtained in mixtures with RHA, which had high apparent electrical resistivity of 257% compared to the reference concrete. Based on the tests performed, it was found that the partial replacement for cement concrete SSA, RHA and BFS gives benefits as regards the apparent electrical resistivity and capillary absorption.